Proceso de atención de enfermería en pacientes con dengue en el centro de salud Caluma Tipo C. septiembre-diciembre 2024 - Pucha Guailla, Carlos Fernando (2025)
This study investigated the application of the Nursing Care Process, focusing on the 14 Virginia Henderson needs, in patients with dengue fever at the Caluma Type "C" Health Center. The main objective was to employ the nursing care process in patients with dengue fever at the Health Center related to the Virginia Henderson model. The methodology used was quantitative, based on an assessment guide that allowed observation, planning, and analysis of data using multiple techniques and instruments appropriate to the human needs of the users and the community studied. Among the results, eight nursing care plans (NCPs) specific to patients with dengue fever were developed, based on nursing diagnoses, which include temperature control, electrolyte administration, pain management, swallowing improvement, and promotion of psychoemotional well-being. These plans have proven to be efficient and positive, improving the physical, psychological, spiritual, and social wellbeing of patients and contributing significantly to their recovery. In conclusion, the research emphasized the importance of tailoring nursing care to the individual needs of each patient, demonstrating that the Virginia Henderson-based model can significantly optimize the quality and quality of care and the health status of patients undergoing dengue treatment.